Theatricality in the horror film : a brief study on the dark pleasures of screen artifice - Loiselle, André (Anthem Press, 2020)
The horror film generally presents a situation where normality is threatened by a monster. From this premise, Theatricality in the Horror Film argues that scary movies often create their terrifying effects stylistically and structurally through a radical break with the realism of normality in the form of monstrous theatricality. Theatricality in the horror fi lm expresses itself in many ways. For example, it comes across in the physical performance of monstrosity: the overthe-top performance of a chainsaw-wielding serial killer whose nefarious gestures terrify both his victims within the film and the audience in the cinema. Theatrical artifice can also appear as a stagy cemetery with broken-down tombstones and twisted, gnarly trees, or through the use of violently aberrant filmic techniques, or in the oppressive claustrophobia of a single-room setting reminiscent of classical drama. Any performative element of a film that flaunts its difference from what is deemed realistic or normal on screen might qualify as an instance of theatrical artifice, creating an intense affect in the audience. This book argues that the artificiality of the frightening spectacle is at the heart of the dark pleasures of horror